Território e Poder: a produção agroecológica como estratégia de desenvolvimento territorial - Gaiovicz, Elaine Fabiane (2011)
The so-called modernization of agriculture constituted a period of intensification of the process of environmental degradation and significant changes in labor relations. Among the movements of resistance to the standardization of production, it emerged the agroecology, which in some municipalities of the Southwest of Paraná, such as Verê, progressively generated considerable results. The agroecology is concerned with the production of healthy food, human health and the preservation of the environment. It promotes the creation of new networks characterized by different rhythms and times, it organises the elements of the geographic space accordingly to a specific pattern, based on the inputs of the collectivity, while respecting the local culture, policy, environment and economy. In this way, new networks, flows and assets were included in the process of territorialization of the agroecology, which gradually develops with the support of associations such as the APAV and APROVIVE, ngos, namely CAPA and ASSESOAR, and certification bodies as REDE ECOVIDA, who play an important role together with local farmers. For these reasons, we aim to understand the agroecological approach adopted by some family farms in Verê, as a way of producing that establishes alternative systems to the ones claimed by the Green Revolution; moreover, we prove the existence of forms of submission and mechanisms of control of family farmers, throughout an integrated farming system where poultry are raised, which is backed by the enterprise Sadia Unit of Dois Vizinhos; and finally, we intend to analyze the existence of a political organization and to produce a map of the agrocological family farms existing in Vere. With this purpose, we started with a literature review, and followed up with field work in the agroecological farms in the municipality of Verê and in a farm integrated to the Sadia, calling for the support of all partner agencies involved with organic production, and conducting interviews with farmers, integrated poultry raisers, representatives and managers of each institution. After collecting data, we drew a map illustrating the farms, the quantitative and qualitative synthetic frameworks, the sketches representing five farms and the theoretical conclusions with regard to the territorial resistance movement promoting agroecology, specifically in Verê. Finally, we conclude that this production system still faces many challenges, however these can and have to be overcome, in order to contribute to local development, sustainability and quality of life